(untitled) (TEST BioLaw Journal - Rivista di BioDiritto, 2025)
Administrative detention must be looked at as a system. It relies on the privatisation of management services, including health care, leading to critical issues regarding transparency, accountability and public health. This contribution provides an overview of the relationship between public and private sectors in the CPR, with a focus on the ambiguities encountered in the contracts and on the consequences related to possible conflicts of interest of healthcare personnel. It is crucial, in analysing the CPR system, to frame the total institution from a broader perspective, asking the right questions and investigating the deep historical meaning of administrative detention.